An interactive computer‐based simulation system for endovascular aneurysm repair surgeries. (19th April 2016) - Wang, Yanzhen; Serracino‐Inglott, Ferdinand; Yi, Xiaodong; Yang, Xue‐Jun; Yuan, Xue‐Feng
Abstract: This paper presents an interactive simulation system for surgical procedures of endovascular aneurysm repair. It extracts anatomical structure of clinic interest from patient‐specific X‐ray computed tomography or magnetic resonance imaging data by image segmentation techniques, and then reconstructs surface triangular meshes of these anatomical structures from the volumetric data. The core of the system is an interactive computer‐based simulation module. It consists of a physical modeling unit, a collision detection unit, a visualization unit, and a control unit. The integration of these units together makes it possible for users to interact with the system in real time, performing virtual catheterization, angiography, and stent graft deployment under a user‐specified rendering mode. The prototype system can be used as a cost‐efficient tool for surgical planning with patient‐specific anatomical geometry and for practice of surgical procedures before actual operation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents an interactive computer‐based simulation system for surgical procedures of endovascular aneurysm repair. It converts patient‐specific medical imaging data into a personalized virtual surgical environment, upon which efficient and stable modeling methods are developed for real‐time simulation of catheterization, angiography, and stent graft deployment operations. An interactive feature is achieved through multi‐modal feedbacks including both visual and haptic renderings integrated with the simulation hardware platform